Augustine and Contemporary Republicanism: On Speech as Domination. (March 2020) - Kabala, Boleslaw Z.
I argue that Augustine can inform contemporary republicanism in a way that has not yet been considered: by means of the utility of "overlapping consensus." I first unpack Philip Pettit's theory of republicanism and demonstrate that his work contains a significant "blind-spot, " namely, more deliberation is required than Pettit allows to establish "arbitrary" interference in the lives of citizens for the sake of maximizing non-domination. But the deliberative settings leave an opening for domination through rhetoric. It is here that Augustine enters: although both the Confessions and City of God contain multiple striking examples of the use of rhetoric, they also provide evidence of a distrust of rhetoric given its potential for domination. It is only in Book IV of De Doctrina Christiana that Augustine lays out explicitly and theoretically a positive use of rhetoric. I then argue that, to minimize domination in the deliberative settings required to better understand the changing definition of "arbitrary" interference, Pettit may profitably look to Augustine's explicit theoretical conceptualization of rhetoric. I end by pointing out that this does not require accepting Augustine's ontology and metaphysics. Indeed, through an overlapping consensus, agreement may be reached on rhetorical practices that do not contribute to domination.